The Balanced Scorecard and Twenty‐First‐Century Thoughts on Motivation. Issue 4 (May 2015) - Albright, Thomas L.; Burgess, Christopher M.; Davis, Stan
Abstract : How can you motivate people to accomplish an organization's goals? Is a carrot‐and‐stick approach the only—or even the best—way? This article suggests an approach that is potentially more effective by focusing less on the traditional approach of rewards versus punishment, relying instead largely on intrinsic motivations to help bring about desired outcomes. These efforts are consistent with the balanced scorecard concepts of goal setting and rewards that have been widely adopted as performance measurement and strategic communication systems since the early 1990s. © 2015 Wiley Periodicals, Inc.